The influence of the friction factor on the slipping of the work-piece from the convex dies at the eccentric upsetting. - Кухарь, В.В.; Николенко, Р.С. (Problems of Tribology, 2015)
Kukhar V.V., Nikolenko R.S. The influence of the friction factor on the slipping of the work-piece from the convex dies at the eccentric upsetting. In the process of eccentric upsetting of cylindrical work-pieces at the high profile of insertions, large degrees of de-formation and low coefficients of friction of forming is accompanied by slipping of work-pieces over the surface of a de-forming instrument. The beginning of slippage is characterized by some degree of deformations, while a further deformation, depending on a plurality of technological factors and boundary conditions can be with a stable forming. Critical degree of de-formation should be considered as one in which there is a complete blank from slipping convex dies, which can lead to loss of unfixed workpiece workspace.The results of studies of the effect of the coefficient of friction at the contact of the stability of the process of cylin-drical billets eccentric convex dies in terms of slipping out of workpiece workspace are presented in the work. Investigations were carried out in a software package for finite element modeling Deform 3D using the method of experiment planning. Re-ceived the information that can help to exclude slipping cylindrical workpiece of convex dies with eccentric upsetting, de-pending on the starting workpiece sizes, characteristics profile dies, the value of the eccentricity and the coefficient of friction at the contact of a convex dies. The regression models are developed, the adequacy of which is confirmed by the values of Fisher's exact test, with a reproducibility - the value of Cochran's Q test.